2012
DOI: 10.1111/j.1468-2273.2012.00529.x
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Occupational Stress and Employee Health and Wellbeing in a Chinese Higher Education Institution

Abstract: Extensive change is evident in higher education in the People's Republic of China but there have been few studies of the effect of work stress on wellbeing in the higher education sector. The main aim of this study is to test and refine the ASSET (‘An Organizational Stress Screening Tool’) model of occupational stress in a sample of 150 academic and non‐academic employees in a Chinese higher education institute. Using partial least squares modelling, the findings showed that job stressors predicted job dissati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…Although not evaluated in the current study, empirical studies in China report increased occupational stress among university employees related to work conditions [18,19]. It is expected that workers with greater work demands will have more stress which can cause them to adopt unhealthy lifestyles that are risk factors for CVDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not evaluated in the current study, empirical studies in China report increased occupational stress among university employees related to work conditions [18,19]. It is expected that workers with greater work demands will have more stress which can cause them to adopt unhealthy lifestyles that are risk factors for CVDs.…”
Section: Discussionmentioning
confidence: 99%
“…In China, extensive research on MS prevalence has been carried out on the general population [16,17] however limited data is available on workers. In light of risk factors such as heavy workload, long working hours, extended work schedules in Chinese Universities [18,19], and differences in working conditions in comparison to the general population, the health status of university workers merits more attention. Therefore, the objective of this study was to investigate the prevalence of MS and its components among University workers, and determine how the prevalence varied according to sex and occupation.…”
Section: Introductionmentioning
confidence: 99%
“…2,4 Based on interactional perspectives of stress, 5 Cartwright and Cooper 1 proposed the ASSET model of work-related stress to understand relationships between job stressors, health, PWB, and job outcomes. This model proposes that job stressors directly influence health, PWB, and strain, and those who have used the model in empirical research 6 have demonstrated that academic and non-academic higher education employees, for example, experience poorer PWB as a result of job stressors and that enhanced PWB is associated with greater physical wellbeing. The findings of other research in non-sport domains suggest that contract-related factors (e.g., perceived job insecurity) contribute to unfavourable health outcomes (e.g., anxiety, emotional exhaustion) for women in retail, 7 that high demands at work are positively related to poor general health for part-time but not full-time women workers in various labour markets, 8 and that roles and contractual status (i.e., part-versus full-time) influence EU-27 employees' experiences at work.…”
mentioning
confidence: 99%
“…Increasingly, researchers have begun to investigate the well-being of Chinese employees (Huang & Gamble, 2015;Sang, Teo, Cooper, & Bohle, 2013). While available research has often touched upon gender, few studies have focussed specifically on women's work and careers (Cooke & Xiao, 2014), or gender and well-being (Huang & Gamble, 2015).…”
Section: Introductionmentioning
confidence: 99%